-2(4m+5)=-4m-14

Simple and best practice solution for -2(4m+5)=-4m-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4m+5)=-4m-14 equation:


Simplifying
-2(4m + 5) = -4m + -14

Reorder the terms:
-2(5 + 4m) = -4m + -14
(5 * -2 + 4m * -2) = -4m + -14
(-10 + -8m) = -4m + -14

Reorder the terms:
-10 + -8m = -14 + -4m

Solving
-10 + -8m = -14 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
-10 + -8m + 4m = -14 + -4m + 4m

Combine like terms: -8m + 4m = -4m
-10 + -4m = -14 + -4m + 4m

Combine like terms: -4m + 4m = 0
-10 + -4m = -14 + 0
-10 + -4m = -14

Add '10' to each side of the equation.
-10 + 10 + -4m = -14 + 10

Combine like terms: -10 + 10 = 0
0 + -4m = -14 + 10
-4m = -14 + 10

Combine like terms: -14 + 10 = -4
-4m = -4

Divide each side by '-4'.
m = 1

Simplifying
m = 1

See similar equations:

| 9y-2y+8=3y+38+y | | 24=18+4x-6 | | 4z+24+z=29 | | 2x-4=12x-84 | | 2x^2=24x-64 | | 0.5(7x+14)=1.2-(x+2) | | 5k-11+3k=29 | | x^2-8x=64 | | 4x+17=14x-63 | | -2n+6=-6(4n-1) | | 2x+20=52-6x | | 7[-5x-6-5(x+1)]=5x+6 | | 6y+11=2y+59 | | -6(t^2+3)-2(t^2-2)= | | 6(b+9)= | | x^3+2x^2+3x=-6 | | -8x+6(x+8)=36 | | 12=x+4+7x | | 3(1-4x)=-21-6x | | -3(2w-5)=1-4w | | 25x^2+35x=-12 | | -4(2k-3)=4-10k | | 5x+6=30 | | 5(u-7)-7u=-19 | | 2(5x-3)=9x | | 4x-5=x+22 | | 2k+10=7k+5 | | -2+6x=2x-1 | | 7x-13=53-4x | | 9=-3n+6n | | 5x-4(x-7)=3+2x | | 4(a+6)=6+a |

Equations solver categories